Efeitos do microcrédito na geração de renda em microempreendimentos: avaliação de impacto do programa Real Microcrédito - Righetti, Carlos Cesar Buosi (2008)
This doctoral dissertation presents an empirical investigation of microcredit impact on the household income of the micro-entrepreneurs, clients of a commercial Brazilian bank. Real Microcredito belongs to Banco Real, the third largest commercial bank in Brazil, and to Acción International, a non-governmental organization. The research covered a sample of 22.294 microcredit contracts and 20.628 clients, from which 2.366 presented two or more credit operations, from August 2004 to April 2007. The data was provided by Real Microcredito and it was collected on Social and Economic Survey, a questionnaire filled by the microentrepeneur along with the agent, for every credit taken. Average sales was the outcome variable, used to proxy for the household income. Applying the hierarchical linear model (HLM) to analise data it was not possible to confirm with statistical significance that there are changes in the trajectory of sales for the analyzed group. Analyzing inter-individuals differences, it was possible to conclude that the variable feminine gender is associated to the increase of the household sales and income. For the other second-level variables (group-lending, geographic placement and economic activity) it is not possible to identify change statically explained by them. This research presents two contributions to the microfinance knowledge body. Firstly is a methodological contribution: the utilization of Hierarchical Linear Modeling (HLM) for microcredit impact evaluation. This method overcome many existing problems of traditional impact evaluation methods, as control group definition and the possibility of different program participation timing. Secondly is improved evidence. A frequent criticism found at the microfinance literature is the absence of quantitative evaluations with large samples. This work helps to fill this gap. Such conclusions contribute to the academy since they add the above evidences to the microfinance field, which particularly in Asia and for the women, has been highlighted given its society transformation power.